15-deoxy-Δ(12,14) prostaglandin J(2)-induced heme oxygenase-1 in megakaryocytes regulates thrombopoiesis - O’Brien, Jamie J. (2008)
BACKGROUND: Platelet production is an intricate process that is poorly understood. Recently, we demonstrated that the natural PPARγ ligand, 15-deoxy-Δ(12,14) prostaglandin J(2) (15d-PGJ(2)), augments platelet production from megakaryocytes. 15d-PGJ(2) can exert effects independent of PPARγ, by increasing oxidative stress. Herein, we reveal 15d-PGJ(2) affects platelet production by inducing heme-oxygenase-1 (HO-1). OBJECTIVES: To further investigate the influence of 15d-PGJ(2) on megakaryocytes and to understand the role of HO-1 in platelet production. METHODS: Meg-01 cells (a primary megakaryoblastic cell line) and primary human megakaryocytes derived from cord blood were used to examine the effects of 15d-PGJ(2) on HO-1 expression in megakaryocytes and their daughter platelets. The role of HO-1 activity in thrombopoiesis was studied in vitro using established models of platelet production. RESULTS AND CONCLUSIONS: 15d-PGJ(2) potently induced HO-1 mRNA and protein expression in Meg-01 cells and primary human megakaryocytes. The platelets produced from these megakaryocytes also expressed elevated levels of HO-1. 15d-PGJ(2)-induced HO-1 was independent of PPARγ, but could be replicated using other electrophilic prostaglandins, suggesting that the electrophilic properties of 15d-PGJ(2) were important for HO-1 induction. Interestingly, inhibiting HO-1 activity enhanced 15d-PGJ(2)-induced platelet production and reactive oxygen species generation. These new findings support the concept that HO-1 activity is inhibitory for platelet production.